Healthcare accessibility, utilization, and quality of life among internally displaced people during the Sudan war: a cross-sectional study - Hind Elmukashfi ShamsEldin Elobied; Muhannad Bushra Masaad Ahmed; Ahmed Balla M. Ahmed; Romaysa Abdelrahman Hassan Salih; Sohaib Mohammed Mokhtar Ahmed; Abdulhadi M. A. Mahgoub; Abdelmoula Hashim Abdelmagid Mohamed; Eman Hamid Abdallah Elamin; Al-Romaysa M. Osman Khalafalla El-Haj; Mohamed Al-Hadi Hamed Abd-Allah; Arwa Yagoub Elmadani Ibrahim; Yousuf Alnoor Younis Mohamed; et al. (Conflict and Health)
Abstract Background The ongoing war in Sudan has triggered a massive displacement crisis, leaving internally displaced people (IDP) struggling to access healthcare services. This study aimed to investigate healthcare access, utilization, and the quality of life among Sudanese IDP during the conflict. Methods This cross-sectional study was carried out among Sudanese internally displaced people in six states. Quality of life was assessed using the WHOQOL-Bref questionnaire. Accessibility, utilization, and the consequences of not accessing healthcare were evaluated using an author-designed questionnaire, which was piloted prior to the study. Chi-square tests were used to analyze associations between categorical variables, while ANOVA was applied to assess differences in quality-of-life domains based on displacement duration and living conditions. Multinomial logistic regression identified predictors of healthcare affordability, with significance set at p < 0.05. Results Among 612 participants, 40.3% reported facilities being very close, 13.0% faced waits over 2 h, and 54.3% found healthcare unaffordable. Only 33.6% always had access to qualified staff, and 22.8% of IDP visited public healthcare facilities supported by non-governmental organizations. The psychological domain had the highest quality-of-life mean score at 49.7 (18.1). Worsened symptoms (44%) were a common consequence of healthcare inaccessibility, while lack of transport (37.9%) was the most common barrier. Availability of qualified staff significantly increased the likelihood of seeking care (χ² = 11.30, p = 0.022). Quality-of-life domains varied significantly by displacement duration and living situation (p < 0.011). Conclusion This study revealed significant variations in healthcare access and utilization among Sudanese IDP, with quality-of-life domains lower than those of IDP in other countries. Interventions should prioritize innovative solutions like telemedicine, targeted support for vulnerable groups, and expanding health insurance coverage to enhance access and long-term health outcomes.